2010
DOI: 10.1007/s10333-010-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of regression model parameter for constructed wetland using operating data

Abstract: Seven years of performance data from a free surface flow constructed wetland system receiving agricultural runoff were used to determine treatment performance and to develop regression and wetland design models. Removal rates by the wetland were 21-43.6% for 5-day biochemical oxygen demand (BOD 5 ), 49.0-58.1% for total phosphorous (TP), 24.1-46.0% for total nitrogen (TN), and 57.6-77.8% for total suspended solids (TSS). First-order area-based rate constant (k 20 ) values for BOD 5 were 15.48 m/year in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…However, Vymazal (2005) reported that nutrient removal is usually insignificant in CW, does not greater than 50%. On the contrary, Son et al (2010) reported a nitrogen removal efficiency of 53%, and overall observed a two-stage vertical subsurface flow constructed wetland (VSSFCW) performed better nitrogen removal as compared to a single-stage VSS-FCW. Accordingly, in the present study, the two-stage HSSFCW treatment achieved over 77.5% of TN removal at higher HRTs.…”
Section: Pollutant Removal Efficiencymentioning
confidence: 98%
“…However, Vymazal (2005) reported that nutrient removal is usually insignificant in CW, does not greater than 50%. On the contrary, Son et al (2010) reported a nitrogen removal efficiency of 53%, and overall observed a two-stage vertical subsurface flow constructed wetland (VSSFCW) performed better nitrogen removal as compared to a single-stage VSS-FCW. Accordingly, in the present study, the two-stage HSSFCW treatment achieved over 77.5% of TN removal at higher HRTs.…”
Section: Pollutant Removal Efficiencymentioning
confidence: 98%
“…Regarding parameters, the Cin, Cout, HRT, and HLR were assessed since those where the only parameters that were consistently reported in the literature review. The reason behind this preliminary plotting was the fact that multiple studies have been conducted for the removal of pollutants and pathogens from CWs where they perform regression analysis and try to determine if there are significant relationships between the aforementioned parameters [16][17][18][19][20][21][22]. These studies found that there seems to be a linear/nonlinear relationship that is expressed through an equation that is using the Cout as a function of Cin and/or HRT, HLR.…”
Section: Preliminary Exploration Between Parametersmentioning
confidence: 99%
“…Models of varying levels of complexity have been developed and applied to field data to gain insight into the performance of APs. However, many of these models were dedicated to simulating nutrient behavior (Kalin et al, 2013;Son et al, 2010;Sonavane and Munavalli, 2009), and fewer models were assigned to pesticides. Among pesticide fate models are the risk assessment models such as PRZM (Carsel, 1998) and MACRO (Larsbo and Jarvis, 2003;Larsbo et al, 2005), which simulate pesticide fate in the root zone and macro-porous field soils, respectively, and TOXSWA (Adriaanse, 1996) from the FOCUS group (Tooby, 1999), to model pesticide fate in ditches.…”
Section: Introductionmentioning
confidence: 99%